(3cJGH ajg eQShe GdNW heG ENJda ajg bQGA GdCeUGQ heG EJabhG Ydjg ef Pdcs - (3GHf GdGfHGQjs
(3ChdgG (B:s
(3cJHhG GdHSedI HZjQ Cda ShQI aGJMI GdcJGH cJHhG edc jhe GdOjf HZjQ Cda s
(3BNQgG (B:s
(3GdYdb EJabJ eUGMa Cgd GdYQGb SfOY GdRHGfjI HGdYjf ef ZjQ hGh GHf GdGfHGQi hGddg CYde hMSHfG Gddg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdbQGAGJ hGdJLhjOs